Dialyzing paper and preparation method thereof
By using recycled fibers, low-melting polyolefin fibers and safety reinforcers in medical dialysis paper, combined with hot pressing treatment technology, the shortcomings of existing dialysis paper in strength, breathability and biosafety are solved, and higher performance and safer materials are achieved.
Patent Information
- Application Number
- CN202411823654.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-11
AI Technical Summary
While existing medical dialysis papers improve strength and bacteria resistance, there are still insufficient breathability and biosafety, and chemicals used in the production process may be cytotoxic.
Recycled fibers, low-melting polyolefin fibers and reinforcers (such as modified xyloxantan, acrylic copolymers, aqueous polyurethanes) are used to improve the strength and breathability of the dialysis paper through hot pressing, and ensure its biosafety by choosing safe materials and processes.
Higher strength, breathability and antibacterial properties are achieved while reducing bacterial endotoxins and toxicity, ensuring the biosafety of dialysis paper and the reliability of medical applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of paper manufacturing, and in particular, to a dialysis paper and a preparation method thereof. Background Art
[0002] With the rapid development of the medical industry and people's increasing attention to health, higher requirements are placed on the strength, air permeability, heat sealing, antibacterial and other properties of medical dialysis paper. The requirements for Class III medical devices are more stringent. Not only do they need to meet the requirements of antibacterial and air permeability, but they also need to pay attention to the toxicity of the dialysis paper itself to ensure the biosafety of the dialysis paper.
[0003] Chinese patent application CN118272959A discloses a dialysis paper made of chemical fiber with a high-toughness skin-core structure. The strength of the dialysis paper is greatly improved, but its air permeability is also reduced accordingly, and no solution is proposed to the toxicity problem of the dialysis paper itself.
[0004] Chinese patent application CN105970719A discloses a medical dialysis paper, comprising a paper base and a hot melt adhesive layer coated on the upper and lower surfaces of the paper base, wherein the paper base contains 60-65 parts by weight of hardwood raw materials, 30-35 parts by weight of coniferous wood raw materials, 7-10 parts by weight of bamboo charcoal fibers, and 3-5 parts by weight of polyester staple fibers, and the hot melt adhesive layer contains 60-75 parts by weight of ethylene-vinyl acetate copolymer, 15-25 parts by weight of polyamide resin, 1-2 parts by weight of paraffin wax, 1.5-2 parts by weight of antioxidant, 5-8 parts by weight of bamboo charcoal fiber powder, 2-3 parts by weight of barium stearate, 8-15 parts by weight of hydrogenated rosin, 1-1.5 parts by weight of graphite fluoride, and 0.2-0.4 parts by weight of phenyl o-hydroxybenzoate. However, the strength of the medical dialysis paper is still insufficient, and its antibacterial performance is average. Moreover, the chemicals used will be partially dissolved during the sterilization process, showing certain cytotoxicity.
[0005] Chinese patent application CN103498383A discloses a medical dialysis paper, which is made of coniferous wood and hardwood as fiber raw materials according to traditional papermaking technology. Since the hardwood used in this solution has high permeability and the coniferous wood has high strength, the produced medical dialysis paper has good air permeability and strength. However, the medical dialysis paper uses a large amount of wood pulp fiber, which will dissolve β-glucan during steam sterilization, which will affect the detection of bacterial endotoxins.
[0006] Chinese patent application CN117328288A discloses a medical dialysis paper and its production process. The dialysis paper is prepared using viscose fiber, additives and conventional wood pulp fiber. The strength and air permeability of the finished paper are improved by modifying the viscose fiber and changing the beating degree of the wood pulp fiber. However, the wet strength agent PAE (polyamide epichlorohydrin) which is harmful to the human body is used in the production process. Due to the hydrolysis side reaction of epichlorohydrin, organic chlorine is produced, mainly including 1,3-difluoro-2-propanol (DCP) and 3-chloro-1,2-propylene glycol. This type of substance can have adverse effects on the human reproductive system and is considered to be a carcinogenic substance.
[0007] In summary, this field is in urgent need of a new type of dialysis paper to solve the above technical problems.
[0008] In view of this, this application is filed. Summary of the invention
[0009] The purpose of the present application is to provide a composite roller and a preparation method thereof to solve at least one technical problem mentioned in the background technology.
[0010] Specifically, in the first aspect of the present application, a dialysis paper is provided, comprising:
[0011] Recycled fiber 70-75 parts,
[0012] Polyolefin fiber 20-30 parts,
[0013] Enhancer 5-15 parts,
[0014] Wherein, the quantitative of the dialysis paper is 50-85g / m 2 .
[0015] The above technical solution ensures the safety of raw materials by using recycled fibers with less dissolution compared to wood pulp fibers in the prior art; the use of low-melting-point polyolefin fibers can melt the surface of the polyolefin fibers during the hot pressing process, playing a role in bonding surrounding fibers, which is beneficial to improving the strength of the dialysis paper. Recycled fibers have good fiber splitting properties, and low-melting-point multi-branched polyolefin fibers have more fiber branches. By selecting fibers with different freeness for matching, a reasonable paper sheet pore structure can be achieved.
[0016] Preferably, the dialysis paper has a weight of 65-75 g / m 2 .
[0017] Preferably, the content of the enhancer in the dialysis paper is 8-12%.
[0018] Preferably, the regenerated fiber includes at least one of seaweed fiber, lyocell fiber, chitosan fiber, and soy protein composite fiber; the polyolefin fiber is a low-melting-point polyolefin fiber, including at least one of polyethylene fiber, polypropylene fiber, matrix-fibril polyolefin fiber, and parallel polyolefin fiber; the reinforcing agent includes at least one of modified xyloglucan, acrylic copolymer, and water-based polyurethane.
[0019] Preferably, the polyolefin fiber has a thickness of 0.8-15 mg / m, a freeness of 200-600 mL, and a hot melting temperature of 100-150° C. More preferably, the polyolefin fiber is a polyolefin multi-branched fiber. More preferably, the polyolefin fiber has a thickness of 3-10 mg / m, a freeness of 400-500 mL, and a hot melting temperature of 100-135° C.
[0020] In a second aspect of the present application, there is provided a method for preparing the dialysis paper according to the first aspect of the present application, comprising the steps of:
[0021] The step of preparing the pulp M1 is to pulp the regenerated fibers to obtain the pulp M1;
[0022] The step of preparing the slurry M2 is to uniformly disperse the polyolefin fibers to obtain the slurry M2;
[0023] The step of preparing slurry M3 is to mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0024] In the step of obtaining a semi-dry paper web, the mass concentration of the pulp M3 is adjusted to 0.6-0.8%, and the pulp is dehydrated, pressed, and dried to obtain a semi-dry paper web;
[0025] a step of obtaining a semi-finished dialysis paper, wherein the semi-dried paper web is immersed in a reinforcing agent, excess reinforcing agent is driven out of the paper web, and the semi-finished dialysis paper is obtained by drying;
[0026] The step of obtaining the finished dialysis paper is to subject the semi-finished dialysis paper to a heat pressing treatment to obtain the finished dialysis paper.
[0027] Preferably, in the step of obtaining a semi-dry paper web, a Fourdrinier multi-cylinder paper machine is used to achieve dehydration, pressing and drying.
[0028] Preferably, in the step of obtaining the semi-finished dialysis paper, a two-roll extruder is used to drive out excess reinforcing agent from the paper web.
[0029] Preferably, the freeness of the M1 slurry is 250-350 mL and the coarseness is 0.2-0.35 mg / m.
[0030] Preferably, the polyolefin fiber has a thickness of 0.8-15 mg / m, a freeness of 200-600 mL, and a hot melting temperature of 100-150° C. More preferably, the polyolefin fiber is a polyolefin multi-branched fiber. More preferably, the polyolefin fiber has a thickness of 3-10 mg / m, a freeness of 400-500 mL, and a hot melting temperature of 100-135° C.
[0031] Preferably, the reinforcing agent is at least one emulsion of modified xyloglucan, acrylic copolymer, and aqueous polyurethane, and the mass concentration of the emulsion is 15-20%.
[0032] Preferably, the dryness of the semi-dry paper web is 50-80%, preferably 60-65%.
[0033] Preferably, in the step of obtaining the finished dialysis paper, the hot pressing temperature of the semi-finished dialysis paper is 130-140°C.
[0034] Preferably, the weight of the finished dialysis paper is 50-85 g / m 2 More preferably, the weight of the finished dialysis paper is 65-75 g / m 2 .
[0035] In summary, this application has the following beneficial effects:
[0036] First, the dialysis paper provided in the present application has better strength, air permeability and antibacterial properties, lower bacterial endotoxins and toxicity, and better biosafety through the ratio of components such as recycled fibers, polyolefin fibers, and reinforcing agents, thereby ensuring its reliability when used as a medical device and avoiding foreign body reactions during surgery.
[0037] Second, the dialysis paper provided by the present application uses recycled fibers with less dissolution, which ensures the safety of raw materials compared to wood pulp fibers in the prior art; the use of low-melting-point polyolefin fibers can melt the surface of the polyolefin fibers during the hot pressing process, playing a role in bonding surrounding fibers, which is beneficial to improving the strength of the dialysis paper. Recycled fibers have good fiber splitting characteristics, and low-melting-point multi-branched polyolefin fibers have more fiber branches. By selecting fibers with different freeness for matching, a reasonable paper sheet pore structure can be achieved.
[0038] Third, the preparation method of dialysis paper provided in the present application, by preparing M1, M2, and M3 of each component separately, and successively preparing semi-dry paper webs and semi-finished dialysis paper, can make the obtained dialysis paper have better strength, air permeability and biosafety. DETAILED DESCRIPTION
[0039] Here, exemplary embodiments will be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.
[0040] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0041] The present application will be described in detail below through examples.
[0042] With the rapid development of the medical industry and people's increasing attention to health, higher requirements are placed on the strength, air permeability, heat sealing, antibacterial and other properties of medical dialysis paper. As a Class III medical device, medical dialysis paper has more stringent quality requirements. It not only needs to meet the requirements of antibacterial and air permeability, but also needs to pay attention to the toxicity of the dialysis paper itself to ensure the biosafety of the dialysis paper.
[0043] In view of this, in order to solve the existing technical problems in the background technology, the invention concept of the present application is to provide a dialysis paper and a preparation method thereof, wherein the dialysis paper comprises: 70-75 parts of recycled fiber, 20-25 parts of polyolefin fiber, and 5-15 parts of reinforcing agent, wherein the dialysis paper has a basis weight of 50-85g / m 2 .
[0044] According to the invention, by using recycled fibers with less dissolution, the safety of raw materials is guaranteed compared with wood pulp fibers in the prior art; the use of low-melting-point polyolefin fibers can melt the surface of the polyolefin fibers during the hot pressing process, playing a role in bonding surrounding fibers, which is beneficial to improving the strength of the dialysis paper. Recycled fibers have better fiber splitting characteristics, and low-melting-point multi-branched polyolefin fibers have more fiber branches. By selecting fibers with different freeness for matching, a reasonable paper sheet pore structure can be achieved.
[0045] Further, based on the disclosure of this application, the most widely used traditional wet strength agent is polyamide epichlorohydrin (PAE), which can effectively improve the wet strength of paper sheets, but it is also harmful to the human body and the environment, because during its production process, due to the hydrolysis side reaction of epichlorohydrin, organic chlorine will be produced, mainly including 1,3-difluoro-2-propanol (DCP) and 3-chloro-1,2-propanediol, which can cause adverse effects on the human reproductive system and are considered to be carcinogenic substances. In this application, low-melting-point polyolefin multi-branched fibers are added as reinforcing fibers, so wet strength agents can no longer be used, there is no possibility of toxicity, and the addition of hazardous substances is eliminated from the source, ensuring the biological safety of dialysis paper.
[0046] Furthermore, in the field of medical dialysis paper, the current existing technology will experiment with sizing methods to treat paper sheets during the production process to achieve a water-resistant effect. The additives used are mostly starch, alkyl ketene dimer or a mixture of the two. These substances will dissolve harmful substances during high-temperature sterilization. These substances have certain cytotoxicity. Once attached to medical devices, they will cause hemolysis and certain abnormal toxicity in the body after surgery, increasing the risk of medical accidents. The present invention uses acrylic emulsion as an enhancer, which not only shows excellent water resistance, but also has high safety because it meets FDA certification.
[0047] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods. Those skilled in the art should also understand that the reaction time and component feeding involved in this application cannot be absolutely accurate in the actual production process, but are all within the allowable error range. For example, if you want to heat the sample for 30 minutes, the actual operation may be 1 second more or less than 1 second in 30 minutes; if you want to weigh 30g of sample, you may actually weigh 30.001g or 29.998g.
[0048] Unless otherwise specified, all raw materials involved in this application are commercially available products.
[0049] Example 1
[0050] 75 parts of seaweed fibers were pulped to obtain pulp M1 with a freeness of 250 mL and a coarseness of 0.3 mg / m;
[0051] 25 parts of low-melting-point polyethylene fibers with a thickness of 8 mg / m and a freeness of 400 mL are evenly dispersed to obtain slurry M2, wherein the melting point of the low-melting-point polyethylene fibers is 135° C.;
[0052] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0053] The mass concentration of the pulp M3 is adjusted to 0.6%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 60%;
[0054] The semi-dried paper sheet is immersed in a reinforcing agent acrylic acid copolymer with a mass concentration of 15%, and then the excess reinforcing agent of the paper sheet is driven out by a two-roll extruder, and the semi-finished dialysis paper is obtained by drying;
[0055] The semi-finished dialysis paper was heat-pressed at 130°C to obtain a quantitative 70g / m 2 The dialysis paper product was prepared; and the content of acrylic acid copolymer in the finished paper was measured to be 8%.
[0056] Example 2
[0057] 70 parts of lyocell fibers were pulped to obtain pulp M1 with a freeness of 350 mL and a coarseness of 0.2 mg / m;
[0058] 30 parts of low-melting-point polyethylene fibers with a thickness of 3 mg / m and a freeness of 500 mL are evenly dispersed to obtain slurry M2, wherein the melting point of the low-melting-point polyethylene fibers is 100° C.;
[0059] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0060] The mass concentration of the pulp M3 is adjusted to 0.6%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 65%;
[0061] The semi-dried paper sheet is immersed in a reinforcing agent acrylic acid copolymer with a mass concentration of 15%, and then the excess reinforcing agent is driven out of the paper sheet by a two-roll extruder, and then dried to obtain a semi-finished dialysis paper;
[0062] The semi-finished dialysis paper was heat-pressed at 130°C to obtain a quantitative 75g / m 2 The finished dialysis paper was prepared; and the content of acrylic acid copolymer in the finished paper was measured to be 9%.
[0063] Example 3
[0064] 75 parts of chitosan fibers were pulped to obtain pulp M1 with a freeness of 350 mL and a coarseness of 0.2 mg / m;
[0065] 25 parts of polypropylene fibers with a coarseness of 2 mg / m and a freeness of 300 mL are evenly dispersed to obtain slurry M2, wherein the melting point of the polypropylene fibers is 150° C.;
[0066] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0067] The mass concentration of the pulp M3 is adjusted to 0.6%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 65%;
[0068] The semi-dried paper sheet is immersed in a reinforcing agent water-based polyurethane with a mass concentration of 20%, and then the excess reinforcing agent is driven out of the paper sheet by a two-roll extruder, and then dried to obtain a semi-finished dialysis paper;
[0069] The semi-finished dialysis paper was heat-pressed at 130°C to obtain a quantitative 50g / m 2 Finished dialysis paper; and the content of acrylic acid copolymer in the finished paper was measured to be 12%.
[0070] Example 4
[0071] 70 parts of lyocell fibers were pulped to obtain pulp M1 with a freeness of 350 mL and a coarseness of 0.2 mg / m;
[0072] 20 parts of polypropylene fibers with a coarseness of 5 mg / m and a freeness of 500 mL are evenly dispersed to obtain slurry M2, wherein the melting point of the polypropylene fibers is 125° C.;
[0073] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0074] The mass concentration of the pulp M3 is adjusted to 0.8%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 65%;
[0075] The semi-dried paper sheet is immersed in a reinforcing agent acrylic acid copolymer with a mass concentration of 15%, and then the excess reinforcing agent is driven out of the paper sheet by a two-roll extruder, and then dried to obtain a semi-finished dialysis paper;
[0076] The semi-finished dialysis paper was heat-pressed at 140°C to obtain a quantitative 65g / m 2 The finished dialysis paper was prepared; and the content of acrylic acid copolymer in the finished paper was measured to be 9%.
[0077] Example 5
[0078] 75 parts of seaweed fibers were pulped to obtain pulp M1 with a freeness of 300 mL and a coarseness of 0.35 mg / m;
[0079] 25 parts of low-melting-point polyethylene fibers with a thickness of 10 mg / m and a freeness of 400 mL are evenly dispersed to obtain slurry M2, wherein the melting point of the low-melting-point polyethylene fibers is 100° C.;
[0080] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0081] The mass concentration of the pulp M3 is adjusted to 0.8%, and a fourdrinier multi-cylinder paper machine is used to dewater, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 60%;
[0082] The semi-dried paper sheet is immersed in a reinforcing agent water-based polyurethane with a mass concentration of 20%, and then the excess reinforcing agent is driven out of the paper sheet by a two-roll extruder, and then dried to obtain a semi-finished dialysis paper;
[0083] The semi-finished dialysis paper was heat-pressed at 135°C to obtain a quantitative 70g / m 2 Finished dialysis paper; and the content of acrylic acid copolymer in the finished paper was measured to be 11%.
[0084] Comparative Example 1
[0085] 75 parts of coniferous pulp fibers were subjected to beating treatment with a beating degree of 25SR to obtain pulp M1;
[0086] 25 parts of hardwood pulp fibers were subjected to beating treatment with a beating degree of 27SR to obtain pulp M2;
[0087] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0088] The mass concentration of the pulp M3 is adjusted to 0.8%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 65%;
[0089] The semi-dry paper sheet is coated with a mixed solution of alkyl ketene dimer and modified starch, and then dried to obtain a dialysis paper product.
[0090] Comparative Example 2
[0091] 75 parts of coniferous pulp fibers were subjected to beating treatment with a beating degree of 25SR to obtain pulp M1;
[0092] 25 parts of hardwood pulp fibers were subjected to beating treatment with a beating degree of 27SR to obtain pulp M2;
[0093] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0094] The mass concentration of the pulp M3 is adjusted to 0.8%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 65%;
[0095] The semi-dry paper sheet is coated with the modified starch solution and dried to obtain the finished dialysis paper.
[0096] Comparative Example 3
[0097] 75 parts of coniferous pulp fibers were subjected to beating treatment with a beating degree of 30SR to obtain pulp M1;
[0098] 25 parts of hardwood pulp fibers were subjected to beating treatment with a beating degree of 32SR to obtain pulp M2;
[0099] Mix slurry M1 and slurry M2 evenly to obtain slurry M3;
[0100] The mass concentration of the pulp M3 is adjusted to 0.6%, and a fourdrinier multi-cylinder paper machine is used to dehydrate, press, and dry the pulp to obtain semi-dry paper sheets with a dryness of 65%;
[0101] The semi-dry paper sheet is coated with a mixed solution of alkyl ketene dimer and modified starch, and then dried to obtain a dialysis paper product.
[0102] Example 6 Physical index test
[0103] The dialysis papers obtained by the methods of Examples 1-5 and Comparative Examples 1-3 were used as samples to test tensile strength and air permeability:
[0104] Tensile strength: The test method adopts GB / T453-2002 "Determination of tensile strength of paper and paperboard";
[0105] Air permeability: The test method adopts GB / T458-2008 "Determination of air permeability of paper and paperboard";
[0106] The test data are recorded as shown in Table 1:
[0107] Table 1 Physical index test results of Examples 1-5 and Comparative Examples 1-3
[0108]
[0109] According to the results in Table 1, we can see that:
[0110] First, the dialysis paper obtained in Examples 1-5 has a strength greater than 90 N.m / g, which has a relatively high strength and further reduces the risk of package rupture;
[0111] Second, the air permeability of the dialysis paper obtained in Examples 1-5 is greater than 10 μm.(Pa.s) -1 , showing good air permeability, which is beneficial to the sterilization of medical devices.
[0112] Third, the tensile index and air permeability of Example 3 are slightly lower than those of other examples. It is speculated that the physical properties of the polyolefin fiber selected affect the quality indicators of the final product.
[0113] Based on the above, in Examples 1-5, the experimental fiberization of the regenerated fibers is stronger and the low-melting-point polyolefin multi-branched fibers are more evenly interwoven during the molding process. Through hot pressing treatment, the surface of the low-melting-point polyolefin multi-branched fibers melts and bonds to the surrounding fibers, thereby improving the tensile strength of the paper sheet.
[0114] Comparative Examples 1-3 use traditional coniferous wood pulp and broadleaf pulp for blending. The strength of the paper sheet mainly relies on the hydrogen bonding between the fibers. If the strength needs to be improved, it can only be done by increasing the fiber beating degree, such as the solution in Comparative Example 3. However, although increasing the beating degree can improve the strength of the paper sheet, it will also make the paper sheet denser, thereby reducing the air permeability of the paper sheet, and cannot take into account both the air permeability and strength indicators of the dialysis paper.
[0115] Example 7 In vitro hemolysis test
[0116] The dialysis paper obtained by the methods of Examples 1-5 and Comparative Examples 1-3 was used as a sample for an in vitro hemolysis test: According to ISO 1993-4:2017:
[0117] Experimental animals: New Zealand white rabbits (healthy, male), from Shanghai Songjiang District Chedun Experimental Animal Breeding Farm Co., Ltd., license number: SCXK (Shanghai) 2022-0001, quality certificate number: 20220001001461.
[0118] Negative control: 0.9% sodium chloride injection, purchased from Shandong Qidu Pharmaceutical Co., Ltd.
[0119] Positive control: distilled water, purchased from Guangzhou Watsons Food and Beverage Co., Ltd.
[0120] Test content:
[0121] Preparation of fresh anticoagulated rabbit blood: Mix rabbit blood and 0.9% sodium chloride injection in a volume ratio of 4:5. Collect 10 mL of blood from a healthy adult rabbit and use 2% potassium oxalate for anticoagulation to prepare fresh anticoagulated rabbit blood.
[0122] Preparation of diluted blood: Take 8 mL of fresh anticoagulated rabbit blood and add 10 mL of 0.9% sodium chloride injection to dilute it.
[0123] Sample preparation: Weigh 3 portions of the test sample, 5 g each, cut them into 5 cm long sections, and prepare 3 portions for testing according to the ratio (sample: contact liquid volume).
[0124] Three centrifuge tubes were taken for the negative control group and the positive control group, and 10 mL of 0.9% sodium chloride injection and distilled water were added to each tube.
[0125] Test steps: Add 5g of test sample to each tube of the test sample group, and then add 10mL of sodium chloride injection; add 10mL of sodium chloride injection to each tube of the negative control group; add 10mL of distilled water to each tube of the positive control group. Operate 3 tubes in parallel for each group. Place all test tubes in a constant temperature water bath at 37℃±1℃. After keeping warm for 30 minutes, add 0.2mL of diluted rabbit blood to each test tube, mix gently, and continue to keep warm in a 37℃±1℃ water bath for 60 minutes. Pour out the solution in the tube and centrifuge at 800g for 5 minutes. Aspirate the supernatant and pour it into a cuvette, and use a spectrophotometer to measure the absorbance of each group at a wavelength of 545nm.
[0126] Statistical method: The absorbance of the test sample group and the control group is the average of 3 tubes. The absorbance of the negative control tube should not be greater than 0.03, and the absorbance of the positive control should be 0.8±0.3, otherwise the test should be repeated. The hemolysis rate calculation formula is as follows:
[0127]
[0128] The test results are shown in Table 2.
[0129] Table 2 In vitro hemolysis test results of Examples 1-5 and Comparative Examples 1-3
[0130]
[0131] According to the test results in Table 2:
[0132] The hemolysis rates of the test samples of Examples 1-5 were all less than 5%, which met the standard requirements; while the hemolysis rates of the test samples of Comparative Examples 1-3 were all greater than 5%, which did not meet the standard requirements.
[0133] The dialysis paper provided in the present application has a lower hemolysis rate and is safer to use.
[0134] Example 8 In vitro cytotoxicity test
[0135] Test basis: GB / T 16886.5-2017 "Biological evaluation of medical devices Part 5: In vitro cytotoxicity test"
[0136] Reference substance: high density polyethylene.
[0137] Test solvent (MEM complete culture medium): 180 mL MEM basic culture medium + 20 mL fetal bovine serum.
[0138] Experimental cells: Mouse fibroblast L-929, from the Cell Bank of the Chinese Academy of Sciences.
[0139] Pretreatment method of the test sample: take a surface area of 30cm 2The sample dialysis paper was placed in a glass container, sterilized at 115℃ for 30min, and then MEM complete culture medium was used as the extraction solution. 2 / mL ratio of MEM complete culture medium 10mL, in a constant temperature oscillator, 1000rpm, to prepare a 100% test sample extract. Blank control pretreatment method: aspirate 10mL MEM complete culture medium, in a constant temperature oscillator, 100rpm, 37℃ conditions for extraction for 24h.
[0140] Pretreatment method for negative control: weigh 2.0012g high-density polyethylene, wash it clean, dry it with filter paper and place it in a glass container. After high-pressure sterilization at 115℃ for 30min, use MEM complete culture medium as the extraction medium, add 10mL of MEM complete culture medium at a ratio of 0.2g / mL, and extract for 24h in a constant temperature oscillator at 100rpm and 37℃.
[0141] Preparation method of positive control: aspirate 1 mL DMSO, add 9 mL MEM complete culture medium, mix well, and obtain 10 mL positive control solution containing 10% DMSO.
[0142] Experimental method: L-929 cells were cultured with MEM complete medium. When the cells were nearly confluent, they were digested with 0.25% trypsin-EDTA and made into 1×10 5 / mL cell suspension; the cell suspension was inoculated in a 96-well culture plate, with 6 parallel wells in each group, 100 μL in each well, and MEM complete culture medium was added to the peripheral wells of the 96-well plate, 100 μL in each well, and cultured in a 37°C, 5% CO2 incubator for 24 hours; the original culture medium was discarded, and fresh complete culture medium was added to the blank control group, the negative control group was added with negative control extract, the positive control group was added with positive control solution, and the 100% test sample extract group was added with 100% test sample extract, 100 μL / well, and cultured in a CO2 incubator for 24 hours before observing the cell morphology under a microscope; the original culture medium was discarded, 50 μL of MTT solution was added to each well, and after continuing to culture for 2 hours, the plate was carefully shaken, the MTT solution was aspirated and discarded, 100 μL of isopropanol was added to each well, and the absorbance of each well was measured with an enzyme marker, the measuring wavelength was 570 nm, and the reference wavelength was 650 nm.
[0143] Data statistical method: The original data is expressed as the mean plus or minus the standard deviation. 570 If the average value is ≥ 0.2 and the difference between the average values of the blanks in the left and right columns and the average value of all blanks is not greater than 15%, and the survival rate of 50% test sample extract is ≥ 100% test sample extract, the test system is established and the degree of cytotoxic reaction of the test sample is analyzed and determined, otherwise the test is repeated.
[0144] Calculation of cell viability:
[0145]
[0146] Note: OD570e - average absorbance of the sample group (negative, positive); OD570b - average absorbance of the blank control group.
[0147] Cell toxicity judgment: If the cell viability of the 100% test article extract group > 70%, the test article has no cell toxicity.
[0148] The test results are shown in Table 3.
[0149] Table 3 Test results of in vitro cell toxicity of Examples 1 - 5 and Comparative Examples 1 - 3
[0150]
[0151] According to the results in Table 3:
[0152] The dialysis paper prepared in Examples 1 - 5 was subjected to in vitro cell toxicity test, and the results showed that the cell viability was greater than 90%, far higher than 70%, proving that the dialysis paper has no cell toxicity; while for the dialysis paper prepared in Comparative Examples 1 - 3, the in vitro cell toxicity test results showed that the cell viability was less than 70%, proving that the dialysis paper has certain cell toxicity.
[0153] Example 9 Abnormal toxicity test
[0154] The test was based on the "Abnormal Toxicity Test Method" in General Principles 1141 of the Third and Fourth Volumes of the Chinese Pharmacopoeia 2020 Edition.
[0155] Test system:
[0156] NIH mice, SPF grade, male, 45, provided by Guangdong Provincial Medical Experimental Animal Center. Experimental animal production license number: SCXK(Guangdong)2022 - 0002. Experimental animal quality certificate number: 44007200129006. Animal use license number: SYXK(Guangdong)2022 - 0002. Animal experiment certificate number: 00391247.
[0157] Hartley guinea pigs, SPF grade, male, 18, provided by Guangdong Provincial Medical Experimental Animal Center. Experimental animal production license number: SCXK(Guangdong)2022 - 0002. Experimental animal quality certificate number: 44007200129007. Animal use license number: SYXK(Guangdong)2022 - 0002. Animal experiment certificate number: 00391246.
[0158] Preparation method of test article: Take an appropriate amount of test article, at 50L / m 2After rinsing and filtering with purified water, take a small amount of purified water for extraction at 100°C and take the extract for testing.
[0159] The test results are shown in Tables 4 and 5.
[0160] Table 4-1 Abnormal toxicity test results of Example 1-5 (mouse test method)
[0161]
[0162]
[0163] Table 4-2 Abnormal toxicity test results of comparative examples 1-3 (mouse test method)
[0164]
[0165] According to the test results in Table 4:
[0166] The extracts of Examples 1-5 were injected into mice, and clinical observation was performed for 7 days, and body weight was recorded. No abnormal reactions were observed in all the groups during the experiment, and all animals gained weight and survived, indicating that Examples 1-5 had no abnormal toxicity and met the standards.
[0167] The extracts of Comparative Examples 1-3 were injected into mice, and clinical observation was performed for 7 days, and the body weight was recorded. All the drug-administered groups developed anorexia, decreased response, diarrhea, polyuria and other symptoms during the experiment, and some animals died. The body weight of all animals decreased, indicating that Comparative Examples 1-3 had certain abnormal toxicity and did not meet the standard requirements.
[0168] Table 5 Abnormal toxicity (guinea pig test method) results of Examples 1-5 and Comparative Examples 1-3
[0169]
[0170] According to the test results in Table 5:
[0171] The extracts of Examples 1-5 were injected into guinea pigs, and clinical observation was performed for 7 days, and the body weight was recorded. No abnormal reactions were observed in all the groups during the experiment, and all animals gained weight and survived, indicating that Examples 1-5 had no abnormal toxicity and met the standards.
[0172] The extracts of Comparative Examples 1-3 were injected into guinea pigs, and the clinical observation was carried out for 7 days, and the body weight was recorded. All the drug-administered groups developed anorexia, diarrhea, polyuria and other symptoms during the experiment. Although no animals died, the body weight of all animals decreased by more than 10%, indicating that Comparative Examples 1-3 had certain abnormal toxicity and did not meet the standard requirements.
[0173] In summary, the dialysis paper and preparation method thereof provided in the present application, and the dialysis paper products obtained therefrom, have high strength and good air permeability, and the products all meet the medical device evaluation standards, have no cytotoxicity, no abnormal toxicity, and will not cause hemolysis. They are products with high biosafety and can solve the technical problems involved in the background technology.
[0174] It should be pointed out that for ordinary technicians in this field, the technical features in the above embodiments can be freely combined, and the formed technical solutions also belong to the embodiments disclosed in this application.
[0175] Furthermore, without departing from the principles of the present application, several improvements and modifications may be made to the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.
Claims
1. A dialysis paper, characterized in that include: Recycled fiber 70-75 parts, Polyolefin fiber 20-30 parts, Enhancer 5-15 parts, Wherein, the quantitative of the dialysis paper is 50-85g / m 2 .
2. The dialysis paper according to claim 1, characterized in that: The regenerated fiber includes at least one of seaweed fiber, lyocell fiber, chitosan fiber, and soybean protein composite fiber; the polyolefin fiber is a low-melting-point polyolefin fiber, including at least one of polyethylene fiber, polypropylene fiber, matrix-fibril polyolefin fiber, and parallel polyolefin fiber; the reinforcing agent includes at least one of modified xyloglucan, acrylic copolymer, and water-based polyurethane.
3. The dialysis paper according to claim 1, characterized in that: The polyolefin fiber has a thickness of 0.8-15 mg / m, a freeness of 200-600 mL, and a hot melting temperature of 100-150° C.
4. The dialysis paper according to claim 3, characterized in that: The polyolefin fiber has a thickness of 3-10 mg / m, a freeness of 400-500 mL, and a hot melting temperature of 100-135° C.
5. The dialysis paper according to claim 1, characterized in that: The dialysis paper has a basis weight of 65-75 g / m 2 .
6. A method for preparing the dialysis paper according to any one of claims 1 to 5, characterized in that: Includes steps: The step of preparing the pulp M1 is to pulp the regenerated fibers to obtain the pulp M1; The step of preparing the slurry M2 is to uniformly disperse the polyolefin fibers to obtain the slurry M2; The step of preparing slurry M3 is to mix slurry M1 and slurry M2 evenly to obtain slurry M3; In the step of obtaining a semi-dry paper web, the mass concentration of the pulp M3 is adjusted to 0.6-0.8%, and the pulp is dehydrated, pressed, and dried to obtain a semi-dry paper web; a step of obtaining a semi-finished dialysis paper, wherein the semi-dried paper web is immersed in a reinforcing agent, excess reinforcing agent is driven out of the paper web, and the semi-finished dialysis paper is obtained by drying; The step of obtaining the finished dialysis paper is to subject the semi-finished dialysis paper to a heat pressing treatment to obtain the finished dialysis paper.
7. The preparation method according to claim 6, characterized in that: The freeness of the M1 slurry is 300-350 mL, and the coarseness is 0.2-0.35 mg / m.
8. The preparation method according to claim 6, characterized in that: The reinforcing agent is at least one emulsion of modified xyloglucan, acrylic copolymer and waterborne polyurethane, and the mass concentration of the emulsion is 15-20%.
9. The preparation method according to claim 6, characterized in that: The dryness of the semi-dry paper web is 50-80%.
10. The preparation method according to claim 6, characterized in that: In the step of obtaining the finished dialysis paper, the hot pressing temperature of the semi-finished dialysis paper is 130-140°C.
Citation Information
Patent Citations
Medical dialyzing paper
CN103498383A
Medical dialyzing paper
CN105970719A
Medical dialyzing paper and production process thereof
CN117328288A
High-toughness sheath-core fiber, medical dialyzing paper and preparation method of high-toughness sheath-core fiber
CN118272959A
Process for preparing high-wet-strength dust-free paper and product
CN111235935A